Planned mode of birth after previous caesarean section and women’s use of psychotropic medication in the first year postpartum: a population-based record linkage cohort study - Fitzpatrick, K; Quigley, MA; Smith, DJ; Kurinczuk, JJ (Cambridge University Press, 2021)
Background: Policy in many high-income settings supports giving pregnant women with previous caesarean section a choice between an elective repeat caesarean section (ERCS) or planning a vaginal birth after previous caesarean (VBAC), provided they have no contraindications to VBAC. Despite the potential for this choice to influence women’s mental health, evidence about the associated effect to counsel women and identify potential targets for intervention is limited. This study investigated the association between planned mode of birth after previous caesarean and women’s subsequent use of psychotropic medications.